The Effects of Covid-19 Pandemic towards Conventional Theaters and online Streaming Services in Indonesia - Sihombing, Lambok Hermanto; Lestari, Puji; Dante T.M, Jonathan (International Journal of Communication and Society, 2022)
The Covid-19 pandemic has drastically disrupted all business sectors in Indonesia such as the arts, cultural, and entertainment industries. This circumstance necessitated the conversion of numerous conventional movie theatres and online streaming providers. This scientific article examined the impact of the pandemic on the entertainment industry, specifically theatres of XXI and CGV and movie streaming; Disney+Hotstar and Netflix.  The qualitative method was used to develop this research. The dataset was taken from the survey taken from McKinsey Company website in 2020 and articles. The authors conducted an analysis of the changes based on two theories; New Media from  Martin Lister, Jon Dovey, Seth Giddings and Kieran Kelly and Uses and Gratification Theory from Katz, Blumler, and Gurevitch. The research findings demonstrate that internet streaming services can meet the entertainment needs of lonely individuals at home and result in a paradigm shift away from the belief that new films are only released in theatres.